Los juegos verbales y el lenguaje oral en los niños del nivel inicial I de la escuela de educación básica Alonso de Mercadillo, de la ciudad de Loja, periodo 2021-2022. - Contento Sigcho, Erika Lisbeth (2022)
Oral language is a communicative function that human beings use to internalize and externalize information that is acquired through interaction with the environment, being crucial during the first years of life, since through it children will begin to accumulate memories and experiences that will allow them to express what they think or feel, making correct use of language. The objective of this research was to determine how verbal games improve oral language in children of the Initial level I of the Alonso de Mercadillo Basic Education school in the city of Loja, period 2021-2022, for its realization an approach was mixed that allowed to collect information qualitatively and quantitatively; descriptive scope, helping to detail the characteristics of the variables and quasi-experimental design because the study group was selected for the convenience of the researcher, likewise, analytical-synthetic methods were used which served in the construction of the theoretical framework; inductive-deductive, contributed to synthesize the conclusions that emerged from the investigation. On the other hand, the PLON-R Test instrument was used on fifteen children aged from 3 to 4 years, showing that 13.33% of children were at a normal language level, after the application of the activity guide called “ The magical world of words” through the use of verbal games, a significant change was noted, reaching 66.67% of children at this level. Corroborating that verbal games are effective in strengthening the oral language of infants, noting an improvement in the articulation of phonemes, pronunciation of words, discrimination of sounds, expression of sentences, construction of sentences, engaging in more coherent and understandable conversations. Keywords: communicative function, verbal games, word games, oral language.